2015
DOI: 10.1083/jcb.201410061
|View full text |Cite
|
Sign up to set email alerts
|

BLM helicase facilitates telomere replication during leading strand synthesis of telomeres

Abstract: BLM helicase facilitates telomere replication by resolving G-quadruplex structures that can form in the G-rich repeats during leading strand synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
120
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 133 publications
(123 citation statements)
references
References 60 publications
(116 reference statements)
3
120
0
Order By: Relevance
“…Intriguingly, Stavropoulos and colleagues showed that, in ALT cells, BLM interacts with TRF2 and that overexpression of BLM in ALT cells increases telomeric DNA, suggesting that BLM may play an important role in ALT telomere synthesis (79). The proposed functions of BLM at the telomere include suppressing the fragile-telomere phenotype (16), processing the late-replicating intermediate structure (78), and aiding fork progression possibly through unfolding the G4s (80,81). Here we show that, similar to its role during DSB repair (70), BLM is also required for DNA end resection and HR in our MR-SAT system.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, Stavropoulos and colleagues showed that, in ALT cells, BLM interacts with TRF2 and that overexpression of BLM in ALT cells increases telomeric DNA, suggesting that BLM may play an important role in ALT telomere synthesis (79). The proposed functions of BLM at the telomere include suppressing the fragile-telomere phenotype (16), processing the late-replicating intermediate structure (78), and aiding fork progression possibly through unfolding the G4s (80,81). Here we show that, similar to its role during DSB repair (70), BLM is also required for DNA end resection and HR in our MR-SAT system.…”
Section: Discussionmentioning
confidence: 99%
“…BLM also resolves late replication intermediates and prevents the formation of ultrafine anaphase bridges (UBFs) at telomeres and common fragile sites (CFSs) (26,29). More recently, BLM has been shown to stimulate polymerization across telomeric G-rich sequences that are replicated by leading-strand synthesis from origin firing within the telomere (27). In spite of the functional overlaps, our study reveals a significant difference between WRN and BLM in coordinating cleavage of the upstream fragment during strand displacement.…”
Section: Discussionmentioning
confidence: 57%
“…Interfering with the integrity of the shelterin complex via changing the levels of TRF1 or TRF2 also induces telomere fragility (Martinez et al 2009;Sfeir et al 2009) and gives rise to T-UFBs (d 'Alcontres et al 2014;Nera et al 2015). TRF1 was shown to protect against fragility by recruiting BLM to the telomeres (Sfeir et al 2009), suggesting that BLM facilitates replication (Drosopoulos et al 2015) or disentangles late-replicating structures at these regions Barefield and Karlseder 2012). In contrast to CFS-UFBs, inhibition of TopIIα by ICRF-193 induces T-UFBs, and TRF1 has been shown to recruit TopIIα to telomeres.…”
Section: Ufbs At Telomeresmentioning
confidence: 99%